The Effect of Gerlach and Ely Model Instructional Modules on Systems Thinking Skills among 6th Grade Elementary Students in Saudi Arabia - Alanazi, Awatif; Khairani, Ahmad Zamri (Journal of Cultural Analysis and Social Change, 2025)
Addressing thinking in classrooms produces lifelong learners who possess self-learning tools and self-motivation to search for and acquire knowledge. The current study aimed to investigate the impact of the Gerlach and Ely Model (GEM) on developing systems thinking skills in science among sixth-grade elementary students in Riyadh, Saudi Arabia. Using a quasi-experimental design, the study sample was randomly selected, comprising 80 students, divided into two groups (40 students as a control group and 40 students as an experimental group). A Systems Thinking Skills Test (STSS) was developed and validated. Additionally, a teacher’s guide (instructional plan) was designed based on the Gerlach and Ely Model. A purposive sampling with random assignment of groups was adopted. Descriptive analysis, Levene’s test and independent sample t-test analyses were used to achieve research goals. The Gerlach and Ely Model was employed to design lesson unit plans on systems thinking skills in Saudi science teaching. The results indicate that the experimental group, as opposed to the control group, experienced meaningful changes on all subscales of systems thinking. Statistically significant differences favoring the experimental group were found on the measures of on three specific skills, including PMI Idea Processing, Redesign and Dynamic Handling of Problems. Analyses of gender revealed that there was no significant difference between scores of males and females, yet males ranked higher in related areas like modeling and redesign. The significance of the study's results lies in their confirmation of improved systems thinking skills in science among Saudi elementary school students. These significant gains confirm the effectiveness of the GEM instructional modules combining cognitive and creative skills in science education.